Signeti 16. stoletja - Vodopivec, Ines (Knjižnica, 2006)
The library of the Franciscan Monastery in Novo mesto keeps 224 early prints from the 16th century in which 175 printers' and publishers' devices were recorded. These were printed between 1501 and 1600 in 88 printers' workshops across Europe. Printers' and publishers' devices, also called signets, were used in the 16th century as trademarks of respective printers and publishers. Spiritual and cultural ideas of the 16th century and intellectual goals of their owners are reflected in the complex humanistic motifs of signets. Most of the 16th century signets can be compared to impresas; they include a symbolic image and a short motto in Latin.This text presents some of the main characteristics of signets registered in Slovenia, such as the meaning, design features and motifs, dating from the early development of print culture in Europe.
Keywords: printing; tiskarstvo; tiskarji; založniki; knjigotržci; 16.st.; tiskarski znaki; signeti; simboli; symbol; emblemi; Frančiškanski samostan (Novo mesto)